Optimasi Dimensi Tebal Awal Pelat Pada Proses Pembengkokan Bentuk Jogged Flange Dengan Simulasi Tiga Dimensi - Choiron, Moch. Agus; Ariseno, Agustinus; Prasetyo, Andika (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2012)
One of the problem of bending process is the final product dimension that it is not agree with the expected results. To reduce trial and error of parametersdesign, designers can utilize computer simulations to predict parameter process virtually and more time-saving analysis. The aim of this study is determine the variations effect of initial blank material thickness to the flange flatness of the final product in the jogged flange process.In order to find the influence on the uneveness of the flange bend, the parameters of plate thickness, flange radius ratio, and flange length ratio are selected. Verification models were created to justify the trend data between modeling and the experimental results.From the result, the elevation difference on uneveness of the flange bendwas obtained. For initial blank material thickness dimensions, it can be seen that the minimum value of the uneveness defect can be obtained by using equal of plate area ratio. The observed increase of the flange radius could be attribute to decrease of uneveness of the flange bend. The increase of plate thickness, uneveness of the flange bend will be decrease.Keywords: initial blank material thickness, jogged flange, uneveness of the flange bend